Singkil dalam Lintasan Sejarah: Identitas Wilayah dan Asal Usul Etnisnya - A. Aslym Combih (Yayasan Abdurrauf Cendekia Nusantara, 2025)
This study aims to trace the origins of the ethnic groups and the various designations of the indigenous peoples inhabiting the Aceh Singkil and Subulussalam regions, as well as to examine the historical processes of migration and assimilation that have shaped their cultural identity. Employing historical research methods, the study follows the stages of heuristics, source verification, interpretation, and historiography. The findings reveal that the name